Determinants of ELAV gene-specific regulation. - Soller, M.; Li, M.; Haussmann, I.U. (Biochemical Society Transactions, 2010)
How RNA-binding proteins recognize their complement of targets in a complex cellular environment remains poorly understood. Sequence degeneracy and redundancy of short motifs at genomic scales have mostly eluded predictions of specific target genes for gene-specific ELAV (embryonic lethal abnormal visual system)/Hu proteins that bind ubiquitous AU-rich motifs. Using the genetic tools of Drosophila, we have analysed binding properties of ELAV in vitro and ELAV-dependent regulation of its major target ewg (erect wing) in neurons. These studies reveal that an integral part of ELAV gene-specific regulation involves combinatorial binding to variably spaced short U-rich motifs on an extensive binding site.